Rotor Flux Estimation of Induction Motor Using Artificial Neural Networks - Kumar, V. Sanjay; Balaga, Harish (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2015)
Rotor flux measurement is needed for the control of induction motor by methods like field oriented control. But it is difficult to measure rotor flux in induction motors. Hence rotor flux is estimated by using neural networks in this paper. Rotor flux is simulated using model equations of induction motor and is compared with output of neural network.